Sosialisasi Pencegahan Covid-19 Pengguna Transportasi Laut Pada Wilayah Kepulauan - Raudha Hakim; Abdul Gaus (Journal Of Khairun Community Services, 2021)
Ports as sea transportation infrastructure have a lot of social interactions because they are the entry and exit points for passengers traveling between islands. The form of anticipation for the prevention of Covid 19 is carried out in the form of socialization to passengers by maintaining distance, washing hands and distributing masks while traveling. Covid-19 Prevention and Control Efforts. The socialization of Covid-19 prevention at ports as a meeting point between land and sea transportation modes is expected to be able to provide understanding to the user or passenger community to continue to apply health protocols while in the port area as an effort to prevent and break the chain of the spread of Covid-19. Several protocols to prevent the spread of Covid-19 in public areas include terminals, ports. The contents of the protocol include ensuring that all public areas post health messages (proper hand washing and coughing / sneezing etiquette) in strategic places such as at the entrance. Inform visitors to use clean personal worship tools, provide means of washing hands with soap (CTPS) with running water in the toilet and providing hand sanitizers at each entrance. Check body temperature at each point of entry and observe the general condition of visitors. The role of the public area manager must be coordinating with the local health office on a regular basis.